Autosomal recessive cholesterol deficiency in a holstein calf - Jacinto, Joana Gonçalves Pontes (2018)
Cholesterol deficiency (CD), a newly identified autosomal recessive inherited genetic defect in Holstein cattle, has been reported to have unresponsive diarrhea as a clinical sign, failure to thrive, hypocholesterolemia and the animals usually die within the first weeks or months of life. CD is caused by a mutation of the bovine apolipoprotein B gene (APOB). The objective of the present report is to describe the clinical and pathological phenotype, understand the steps needed to perform a correct diagnosis and execute a treatment of the affected Holstein calf homozygous for the APOB mutation. One Holstein calf with clinical history of intermittent diarrhea and erosions in the buccal cavity was admitted to the Clinic for Ruminants of Facoltà di Medicina Veterinaria dell’Università degli Studi di Bologna, Italy. Furthermore, there was blood collected from 3 related healthy cows (mother, sister 1, sister 2) and semen from the father. This case report included a full clinical description of the clinical phenotype and pathological phenotype, blood hematological and biochemical analysis, and measurements of cholesterol and triglycerides (TG). The animal suffered a natural death 33 days after the admission to the clinic. A genetic test was performed as described by Menzi et al. (2016) using blood for sampling (affected calf, mother, sister 1, sister 2) and semen (father) to determine the APOB genotype. The calf was confirmed homozygous for the APOB mutation. The father and the mother, as expected, were heterozygous carriers of the APOB mutation and the sisters were free of the APOB mutation. The clinical phenotype of the affected calf included muscular atrophy, retarded growth, and chronic diarrhea. Hypocholesterolemia and low TG concentrations was present in the affected the calf. Additionally, the cholesterol concentration of the mother of the affected calf was also lower. The pathological phenotype of homozygous calf was steatorrhea with a segmental enteritis. Although the animal, whilst alive, did not present neurological signs, the brain presented hyperemia of meningeal vessels and a slight cerebral edema. CD must be considered as a possible differential diagnosis for chronic diarrhea and failure to thrive in Holstein calves with no evidences of primary infections. Confirmation of the associated APOB mutation is needed.